KAJIAN TATA KELOLA PEMERINTAHAN BERBASIS TEKNOLOGI KOMUNIKASI DALAM MEWUJUDKAN REVOLUSI 4.0 DI KABUPATEN KONAWE SELATAN - Liwaul, Liwaul; Taufik, Taufik; Nur, Muhammad Nadzirin; Lestari, Indra (Fakultas Pertanian Universitas Halu Oleo, 2023)
Evaluation of the implementation of SPBE in several regional governments in Southeast Sulawesi Province shows that achievements are not very good. Based on the results of the SPBE evaluation of several regional governments in Southeast Sulawesi Province, it shows that the South Konawe Regency Government is in first place with the predicate